Dimensional latent structure of internet gaming disorder symptoms in four representative surveys of German adolescents: results from taxometric analyses - Kliem, Sören; Fischer, Sebastian; Krieg, Yvonne; Baier, Dirk; Rehbein, Florian (Frontiers in Psychiatry, 2025)
BackgroundA very large amount of research has addressed the issue of the latent status of psychiatric disorders. To our knowledge, no study has analyzed the latent structure of Internet Gaming Disorder (IGD) symptoms.MethodWe used a new taxometric approach developed by Ruscio et al. rather than estimating a putative taxon base rate and using that estimate to generate the taxon comparative data, we estimate CCFI-profiles with each base rate estimate between.025 and.975 in increments of.025. Nine indicators (1. Preoccupation, 2. Withdrawal, 3. Tolerance, 4. Reduce/stop, 5. Continue despite problems, 6. Give up other activities, 7. Escape adverse moods, 8. Deceive/cover up, and 9. Risk/lose) according to the prescriptions of the DSM-5 were used as well as a four-indicator set based on ICD-11. The analyses draw on data from German ninth-grade students collected between 2013 and 2019 as part of a periodic representative survey. Overall, N = 36 630 (response rates: 41.4-68.5%; 50.2% male, 27.3% with migration background) adolescents were reached. The Video Game Dependency Scale (CSAS) was used to assess IGD symptoms in accordance with DSM-5.ResultsRegarding the total sample (DSM-5: CCFI-mean-profile = 0.311; ICD-11: CCFI-mean-profile = 0.175), the male sample (CCFI-mean-profile = 0.162/0.046), and female sample (CCFI-mean-profile = 0.390/0.268), strong support for the superiority of a dimensional model was detected.ConclusionIt seems necessary to define diagnostic thresholds regarding IGD-symptom burden based on external criteria (e.g., IGD-related incapacity to work or truancy). Further studies are necessary to substantiate this result in different samples using different measurement approaches.